2016
DOI: 10.1099/jgv.0.000384
|View full text |Cite
|
Sign up to set email alerts
|

Infection of porcine bone marrow-derived macrophages by porcine respiratory and reproductive syndrome virus impairs phagosomal maturation

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV), a positive-sense, ssRNA virus of the genus Arterivirus, is a devastating disease of swine worldwide. Key early targets of PRRSV infection in pigs include professional phagocytes in the lung, such as alveolar and interstitial macrophages and dendritic cells, the dysfunction of which is believed to be responsible for much of the associated mortality. In order to study the effect of virus infection on phagocyte function, the development of a robust, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…In agreement with previous data, we found that BMM displayed anti-microbial functions such as phagocytosis of bacteria, phagosome acidification and ROS production (Chaudhuri et al, 2016). In rodents, catecholamines were previously shown to increase the phagocytic capacity of macrophages (Baccan et al, 2010;Xiu et al, 2013;Grailer et al, 2014), which was suggested to rely upon b2-AR stimulation (Muthu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous data, we found that BMM displayed anti-microbial functions such as phagocytosis of bacteria, phagosome acidification and ROS production (Chaudhuri et al, 2016). In rodents, catecholamines were previously shown to increase the phagocytic capacity of macrophages (Baccan et al, 2010;Xiu et al, 2013;Grailer et al, 2014), which was suggested to rely upon b2-AR stimulation (Muthu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…PRRSV infection is shown to impair the phagosomal maturation of PAMs [90]. Similar to the previous study [18], our analyses also identified that a great variety of phagocytosis-promoting receptor genes were significantly decreased, implying that PRRSV infection can impair the receptor-mediated uptake process of phagocytosis of PAMs.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike other members of Arterivirus , which have relatively broad tropisms for cells of various origins ( Zhang and Yoo, 2015 ), PRRSV infection is highly restricted to cells of the monocyte-macrophage lineage, such as porcine alveolar macrophages (PAMs) ( Albina et al, 1998 ; Morgan et al, 2014 ), macrophages from the spleen, tonsils, lymph nodes, liver, Peyer’s patches and thymus, as well as peritoneal macrophages from blood and progenitor cells in bone marrow ( Sur et al, 1996 ; Duan et al, 1997a , b ; Wang et al, 2016 ). Moreover, bone marrow-derived dendritic cells and macrophages are susceptible to PRRSV infection in vitro as well ( Chang et al, 2008 ; Chaudhuri et al, 2016 ). Generally, only PAMs in lung are considered to be the primary target of PRRSV in vivo ( Albina et al, 1998 ; Morgan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%